The development of a system that emulates percussion to detect the borders of the liver - Rauch, Hanz Frederick (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.